Enhancing Athletic Programs' Recruitment Success: A Strategic Planning Model of Recruiting - Sean Dwyer (Journal of Applied Sports Management, 2020)
A critical yet understudied element in recruiting success is understanding an athletic program’s strengths and weaknesses relative to influential college choice factors. The purpose of this study is to provide practitioners and researchers with a new approach to assess an athletic program’s recruiting process, improve its effectiveness and efficiency, and close the gap between what student-athletes desire in an athletic program and what the program offers. To achieve that end, collegiate football players (N = 66) at a NCAA FBS school were surveyed using a scale consolidated from past college choice factor scholarship. Exploratory factor analysis using principle-component analysis and Varimax rotation was then used to assess the underlying factor structure of the proposed scale and the commonalities among the 48 scale items. From the results, a strategic recruiting model was created that categorizes college choice factors into a four-quadrant matrix consisting of Urgency, Strength, Support, and Concern components.
Keywords: College Choice Factors; Intercollegiate Athletics; Management; Organizational Behavior; Sport Performance